Importância da origem dos recursos alimentares e estrutura trófica da ictiofauna de riachos rurais : uma abordagem longitudinal. - Silva, Marlene Rodrigues da (2013)
Through diet analysis we evaluated the importance of allochthonous resources for the ichthyofauna in streams. The following questions were raised: (i) Is the consumption of allochthonous resources by fish fauna influenced by streams longitudinal gradient of the streams? (ii) Does the identity of fish species influence the consumption of allochthonous resources? To respond these questions, fish were sampled in the headwaters, middle and mouth of four rural streams belonging to the sub-basin of the Pirapó River, Upper Paraná River basin. Samplings were conducted bimonthly from July 2007 to June 2008, using electrofishing. Fish were identified, measured, and their stomach contents were identified and quantified. We analyzed the diet of 17 species. To examine the influence of the longitudinal gradient on the consumption of autochthonous and allochthonous resources, differences in diet composition of the fish fauna between the headwaters, the middle and the mouth of each stream were tested using the non-parametric multi-response permutation procedure (MRPP). In order to evaluate the influence of species identity on the use of food resources by fish fauna, data of diet composition of the species were ordinated by a detrended correspondence analysis (DCA). The results of the diet composition showed for three of the four streams analyzed, an influence of the longitudinal gradient, with allochthonous resources being more important in the middle stretch, and autochthonous resources in the headwaters and in the mouth. The ordination analysis for the diet of species by stream, and the analysis by species and stretch, indicated that the diet of most species was not significantly changed along the longitudinal gradient, nor between the streams, thus species consumed the same basic resources, just ranging the proportions. As important as the availability of the resources for fish, are the particular characteristics of each species, i.e., the identity, which is the set of characteristics (morphological, physiological, behavioral and ecological requirements) that a species should express, to insure their life cycle.